Teaching English writing with fun to elementary students - Siti Nurkilah (LADU: Journal of Languages and Education, 2021)
Background: Elementary school students often complain on writing assignments from their teachers. As a consequence, the elementary students are not enthusiastic about understanding English writing. Purpose: This study aims to identify the technique of teaching English writing for elementary students. Design and methods: The method used is library research method as an activity carried out systematically to collect, process, and conclude data using certain methods/techniques. Results: The study reveals elementary students in low grade (I, II, III) uses creative writing, media word games and high class (IV, V, VI) uses collaborative writing.